Volume equations for tree species in the tropical dry forest of East Nusa Tenggara, Indonesia - Almulqu, Aah Ahmad (ULIN: Jurnal Hutan Tropis, 2025)
The aims of this study is to develop and validate tree volume prediction models of tree species in East Nusa Tenggara tropical dry forest, Indonesia. Data collection in this study was conducted bymeasuring diameter andheight of trees. Tree species volume equation is estimated using models of Berkhout, Kopezky-Gehrhardt and Hohenadl-Krenn. Selectionof the best models was based on the values of the coefficient of standar deviation (SD), R2 adj, aggregate deviation (AD) and average deviation (AveD), root mean square error (RMSE) and bias. Hohenadl-Krenn and Kopezky-Gehrhardt models were accepted as the best model for tree species in all research sites. The selected volume model for these tree species has Hohenadl-Krenn (V = 0.572 - 0.033Dbh + 0.00106Dbh2 for Binafun and V = 0.683 - 0.0366Dbh + 0.001278Dbh2 for Bonmuti) and Kopezky-Gehrhardt models (V = 0.0502 + 0.000537 Dbh2 for Letkole and V = -0.1776 + 0.000677Dbh2 for Oelbanu).